The effectiveness of television advertising campaigns on generating calls to a national Quitline by Māori. Issue 4 (26th July 2005) - Wilson, N; Grigg, M; Graham, L; Cameron, G
Abstract : Objective: To examine the effectiveness of four mass media campaigns on calls to a national Quitline by Māori (the indigenous people of New Zealand). Methods: Monthly Quitline call data and calls within one hour of a television commercial (TVC) being shown were analysed for the 2002–2003 period. Data on target audience rating points (TARPs) and expenditure on TVCs were also used (n = 2319 TVC placements). Results: Māori were found to register with the Quitline at higher rates during the most intense six campaign months (15% more registrations compared to less intense months). The most effective campaign generated 115 calls per 100 TARPs by Māori callers within one hour of TVC airing (the "Every cigarette" campaign). A more Māori orientated campaign with both health and cultural themes generated 91 calls per 100 TARPs from Māori callers. For these two campaigns combined, the advertising cost per new registration with the Quitline by a Māori caller was NZ30–48. Two second hand smoke campaigns that did not show the Quitline number were much less effective at 25 and 45 calls per 100 TARPs. Conclusions: These television advertising campaigns were effective and cost effective in generating calls to a national Quitline by Māori. Health authorities should continue to explore the use of both "threat appeal" style media campaigns and culturally appropriate campaigns to support Quitline use by indigenous peoples.